An Efficient Image Encryption Using a Dynamic, Nonlinear and Secret Diffusion Scheme (Baghdad Science Journal, 2021)
The growing use of teleThis paper presents a new secret diffusion scheme called Round Key Permutation (RKP) based on the nonlinear, dynamic and pseudorandom permutation for encrypting images by block, since images are considered particular data because of their size and their information, which are two-dimensional nature and characterized by high redundancy and strong correlation. Firstly, the permutation table is calculated according to the master key and sub-keys. Secondly, scrambling pixels for each block to be encrypted will be done according the permutation table. Thereafter the AES encryption algorithm is used in the proposed cryptosystem by replacing the linear permutation of ShiftRows step with the nonlinear and secret permutation of RKP scheme; this change makes the encryption system depend on the secret key and allows both to respect the second Shannon’s theory and the Kerckhoff principle. Security analysis of cryptosystem demonstrates that the proposed diffusion scheme of RKP enhances the fortress of encryption algorithm, as can be observed in the entropy and other obtained values.communications implementing electronic transfers of personal data, require reliable techniques and secure. In fact, the use of a communication network exposes exchanges to certain risks, which require the existence of adequate security measures. The data encryption is often the only effective way to meet these requirements. This paper present a cryptosystem by block for encrypting images, as images are considered particular data because of their size and their information, which are two dimensional nature and characterized by high redundancy and strong correlation. In this cryptosystem, we used a new dynamic diffusion technique called round key permutation, which consists to permute pixels of each bloc in a manner nonlinear, dynamic and random using permutation table calculated according to the master key and sub-keys. We use thereafter the AES encryption algorithm in our cryptosystem by replacing the linear permutation of ShiftRows with round key permutation technique; this changing makes the encryption scheme depend on encryption key. Security analysis of cryptosystem demonstrate that the modification made on using the proposed technique of Round Key Permutation enhances the fortress of encryption  algorithm,  as can be observed in the entropy and other obtained values.